United we stand..divided we fall: Political opposition fragmentation post-Mubarak - Mohamed, Asmaa (AUC Knowledge Fountain, 2018)
This thesis examines the causal factors behind the persistence of opposition fragmentation after the toppling of Mubarak and the collapse of the regime’s throbbing heart, the security apparatus. This is due to the importance of opposition unification not only in the toppling of autocrats but also in the success of any transition towards democracy. More urgency is brought to the puzzle due to the specific nature of the transitional period that was more in favor of different political forces compared to previous periods. This argues that three causal factors were behind the re-fragmentation of the opposition post-Mubarak: the continuation of regime manipulation by the SCAF, the failure of cooperation between youth movements and political parties, and the polarization between Islamists and Secularists.